Clinical and biochemical features of the patient status in early postoperaive period after coronary artery bypass surgery (review) - S. Y. Kambarov; O. A. Semenyuk; M. A. Bugrimova; E. E. Simakov; A. V. Lushkin (Кубанский научный медицинский вестник, 2015)
In cardiac surgery practice has accumulated a great experience and made significant progress in the performance of CABG. At the same time the emergence of a number of specific cases of postoperative complications (atrial fibrillation, renal failure, disorders of acid-base balance and fluid and electrolyte balance) associated with the need to use artificial blood circulation. In this regard, currently the most promising methods of improving the technology of CS recognized the operation on a beating heart, and the use of parallel normothermic perfusion. The analysis of literature indicates only a single study of comparative clinical effectiveness of these methods compared with traditional surgery with cardiopulmonary bypass with cardioplegia.